COVID-19 Vaccination in Italian Children: The Limits of Parental Rights - Maricla Marrone; Benedetta Pia De Luca; Alessandra Stellacci; Luigi Buongiorno; Pierluigi Caricato; Gerardo Cazzato; Davide Ferorelli; Biagio Solarino; Pasquale Stefanizzi; Silvio Tafuri; Ettore Gorini; Michele di Landro; et al. (MDPI AG, 2022)
SARS-CoV-2 vaccination campaigns initially targeted the adult population. After the authorization of the main agencies, including the EMA (European Medicines Agency), the European Vaccination Plan now involves young people between the ages of 12-17 and 5-11. In assessing the child's "best interests", the refusal of vaccination by parents or guardians, in addition to the increased circulation of the virus, is responsible for the risk of social distancing. This reduction in social contacts, particularly during very sensitive ages such as adolescence, has been linked to the increased incidence of psychiatric illness, a significant reason for extending vaccination against SARS-CoV-2 in these younger children. One may consider that government should issue a law that allows the child to decide on the vaccination plan, even without the consent of the parents or guardians, without the need for a judge's ruling. The availability of the child should be the point of reference, according to the National Bioethics Committee, for consent to vaccination. The authors investigate the subject in depth in order to counteract vaccination hesitation, and promote the dissemination of correct scientific information, using every different possible communication tool, as well as social networks and schools.